Radiological aspects of lymphomas and leukaemias affecting the jaws: A systematic review. (7th March 2023) - Gomes, Nathalia Rodrigues; Lima, Lucas Ambrósio; Morais‐Perdigão, Ana Luísa; de Caceres, Cinthia Veronica Bardalez Lopez; Sant'Ana, Maria Sissa Pereira; Pontes, Hélder Antônio Rebelo; Pontes, Flávia Sirotheau Correa; Smit, Chané; van Heerden, Willie F. P.; Robinson, Liam; Brasileiro, Cláudia Borges; Brennan, Peter A.; et al.
Abstract: Background: This systematic review aimed to investigate the radiological features of lymphomas and leukaemias affecting the jaws. Methods: A systematic literature review was conducted using the electronic databases of PubMed, Web of Science and Scopus. Articles that contained sufficient radiographic examinations (periapical, panoramic or computed tomography images) for individual cases were included. Additionally, either immunohistochemical or molecular confirmation was required prior to inclusion. Three authors evaluated and described the image quality and radiological features. Results: From an initial 1079 articles screened, 129 cases were included, containing 88 tomographic, 76 panoramic and 26 periapical examinations. The quality of the majority of images was sufficient for evaluation. Diffuse large B‐cell lymphoma, Burkitt lymphoma, leukemic infiltration, plasmablastic lymphoma and extranodal Natural killer (NK)/T‐cell lymphoma, nasal type were the most common subtypes. Involved teeth presented with mobility in 37.2% of the cases and a provisional diagnosis of inflammatory/infectious dental disease was considered in 49.2% of cases. Computed tomography exams were available for 76% of the cases, with most presented with an osteolytic lesion with ill‐defined borders. Periosteal reactions were uncommon. Conclusion: Lymphoma/leukaemia infiltrates of the jaw bones are usually of high‐grade subtypes and rarely present with periosteal reactions.